TrafC‐AnTabu: AnTabu routing algorithm for congestion control and traffic lights management using fuzzy model. Issue 2 (12th July 2021) - Verma, Ajay; Tandon, Righa; Gupta, Pradeep Kumar
Abstract : Traffic congestion is becoming one of the severe problems around the globe. The rate at which vehicles are increasing is exponentially proportional to more complex issues. Therefore, it becomes necessary to efficiently manage traffic flow to avoid congestion on the roads and other complex problems. In this paper, we have proposed a system model that uses the AnTabu routing algorithm to overcome the severe problem of traffic congestion. We have also implemented a fuzzy model for managing the traffic lights on the road intersections. From the obtained results, it is found that the proposed system model has minimized the average travel time of vehicles and has increased the throughput of vehicles on the road intersections. Abstract : In this paper, we have proposed a system model that uses the AnTabu routing algorithm along with fuzzy model to overcome the traffic congestion problems and managing the traffic lights on the road intersections.